Cognitive Impairment in Patients with Pseudotumor Cerebri Syndrome - Siddharth Kharkar; Robert hernandez; Sachin Batra; Philippe Metellus; Argye Hillis; Michael A. Williams; Daniele Rigamonti (Behavioural Neurology)
Introduction: Patients with Pseudotumor Cerebri Syndrome (PTCS) may complain of difficulty in thinking or concentrating; however there has been little formal cognitive evaluation in this population.